Human infection with avian influenza A(H7N2) virus—Virginia, 2002. Issue 4 (13th March 2018) - Terebuh, Pauline; Adija, Akini; Edwards, Lindsay; Rowe, Thomas; Jenkins, Suzanne; Kleene, Jennifer; Fukuda, Keiji; Katz, Jacqueline M.; Bridges, Carolyn B.
Abstract : Background: In March 2002, an outbreak of low‐pathogenic avian influenza (LPAI) A(H7N2) was detected among commercial poultry operations in Virginia. Methods: We performed a serosurvey of 80 government workers involved in efforts to control the outbreak. Results: One study participant who assisted with disposal of infected birds tested positive for neutralizing antibodies to influenza A(H7N2) by microneutralization assay and H7‐specific IgM antibodies by enzyme‐linked immunosorbent assay (ELISA). The acute infection was temporally associated with an influenza‐like illness that resolved without hospitalization. Conclusion: This study documents the earliest evidence of human infection with an H7 influenza virus of the North American lineage.